Policies and labels for negotiating rights protection for the environmentally displaced in Ghana: the Dagara farmer in perspective. Issue 2 (4th May 2018) - Yelfaanibe, Augustine; Zetter, Roger
Abstract: This paper discusses the issue of rights within the context of contemporary policies and the extent to which they address the challenges confronting environmentally displaced people in Ghana. It also explores the role of labels in the drive toward affording appropriate rights protection for the environmentally displaced. The discussions are an offshoot from two extant studies conducted through interviews and focus group sessions. The objective of the first study was to assess the level of preparedness of government to offer appropriate rights protection to environmentally displaced persons. The second study investigated how migrants, especially those affected by changing environmental condition are able to gain access and negotiate their rights in all the different places they go to. From the studies, it was found that there are no clear policies in Ghana meant to afford rights protection to environmentally displaced people and that the rights of such migrants keep shifting with both time and location. People migrating from areas of environmental scarcity lack the capacity to negotiate for 'better' rights due to weak leadership and the fear of losing courtesies extended to them by the host communities. It concludes that there are ample opportunities within the policy and social environments for supporting and promoting appropriate rights protection for environmentally displaced people. It recommends a shift in the national policy drive toward a rights-based protection with clear blue prints for targeting and addressing the needs of environmentally displaced in Ghana.